Pemanfaatan Limbah Rumah Tangga Minyak Jelantah Melalui Kepul Langsung di Desa Cangkuang Kabupaten Garut - Irawati, Irawati; Pertama, Adinda Puteri; Aulia, Azra Nadhira; Ningrum, Tania; Fujiawati, Azqia Nurul; Al chabibah, Fahima 'Alimatush Sholichah; Ghazali, Muhammad Ridwan; Aditya, Muhammad Yanuar; Zulfaqor, Muhammad Rafhi; Basyir, Luthfi Mochammad; Sagita, Lisa (Yayasan Cendekia Gagayunan Indonesia, 2025)
The improper use of used cooking oil poses serious problems for health and the environment. This community service activity aims to raise awareness and provide solutions for managing used cooking oil in Cangkuang Village, Garut Regency. The method used is socialization and knowledge transfer involving cooperation with used cooking oil collectors. The activity was carried out on August 2-16 as part of the Universitas Muhammadiyah Bandung Community Service Program. The results showed an increase in public understanding of the dangers of used cooking oil and how to overcome them. The community began collecting used cooking oil to be sold to collectors who will process it into biodiesel. This initiative provides environmental solutions as well as economic benefits for residents. This activity demonstrates the potential of a community-based approach in addressing environmental challenges and opening up local economic opportunities.